Correlation between thoracic kyphosis and pulmonary function in elderly - Ueawattanasirikul, Chanya; Boripuntakul, Sirinun; Wonglangka, Khanittha; Pinkaew, Decha (Journal of Associated Medical Sciences, 2020)
Background: Thoracic kyphosis is almost found in the elderly and reduces chest expansion which results in decreasing pulmonary function including lung function and respiratory muscle strength, then, it leads to dyspnea and exercises intolerance in the elderly. Objectives: To evaluate thoracic kyphosis measured by flexicurve method in relation to pulmonary function in elderly. Materials and methods: Sixty-six participants aged 65 years and older were recruited for the study. All participants received basic health screening and underwent thoracic kyphosis measurements using flexicurve method. All subjects went through the lung function tests by using spirometer and respiratory muscle strength measurements by using maximal voluntary respiratory pressures. Pearson’s correlation coefficient was used to analyze the relationships between variables. Results: Thoracic kyphosis was mild positive correlated with lung functions in Forced Vital Capacity (FVC), Forced Expiratory Volume in 1 second (FEV1) and Vital Capacity (VC) parameter (r=0.265, 0.303 and 0.322, respectively, p<0.05) but not with FEV1/FVC ratio (%) (p>0.05). There was no correlation between thoracic kyphosis and respiratory muscle strength (maximal inspiratory pressure (MIP) and maximal expiratory pressure (MEP)) (p>0.05). Conclusion: Thoracic kyphosis measured by the flexicurve method had a mild positive correlation with the lung functions.